BENTURAN ANTARA PENYALAHGUNAAN DONASI DAN PENCEMARAN NAMA BAIK (TINJAUAN SOSIOLOGI HUKUM TERHADAP KASUS AGUS SALIM DAN PRATIWI NOVIYANTHI) - Laela, Nyai Badrul; Sholihah, Syaima Nabilah; Khalimy, Akhmad (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This article explores two major legal issues: alleged embezzlement and defamation in the context of public fundraising. The case centers on Agus Salim, an acid attack survivor, accused of misappropriating IDR 1.5 billion in donations meant for his treatment. If proven, the misuse may constitute embezzlement under Article 372 of the Indonesian Penal Code. Agus denies the charges, stating the funds were unused due to BPJS coverage. The second issue involves a defamation complaint against Pratiwi Noviyanthi, who publicly questioned the fund’s use. Agus filed a police report under Articles 310 and 311 KUHP. This study highlights the legal complexities of managing public donations and the importance of balancing transparency, accountability, and the protection of personal reputation in the digital era.